Research Misconduct Policies of Social Science Journals and Impact Factor - Resnik, David B. (2010)
In this study we gathered data on the misconduct policies of social science journals and combined it with the data from our previous study on journal misconduct policies, which did not include enough social science journals for data analysis. Consistent with our earlier finding, impact factor of the journal was the only variable significantly associated with whether a journal had a formal (written) misconduct policy with an odds-ratio of 1.72 (p < 0.01). We did not find that type of science (physical, biomedical, or social) or publisher had a significant effect on whether a journal had a policy. Another important finding is that less than half of the journals that responded to the survey had a formal misconduct policy.